A LITERATURE REVIEW: AKTIVITAS ANTIBAKTERI TANAMAN OBAT TERHADAP BAKTERI PENYEBAB PNEUMONIA - Sinabutar, Rahel Margarenta; Nurfitriani, Iis; Maharani, Dinda Eka; Riasari, Hesti (Jurnal Buana Farma, 2025)
Pneumonia is an acute respiratory tract infection caused by various pathogenic bacteria, including Streptococcus pneumoniae, Staphylococcus aureus, and Klebsiella pneumoniae. The increasing prevalence of antibiotic resistance among these pathogens highlights the need for alternative therapeutic strategies derived from natural products. This study aimed to review the antibacterial potential of medicinal plants against pneumonia-causing bacteria and their underlying mechanisms. A systematic literature review was conducted by searching scientific articles in Google Scholar, PubMed, ScienceDirect, and MDPI. Articles were selected based on inclusion criteria covering antibacterial activity, active compounds, and reported mechanisms of action. A total of 30 eligible articles were analyzed descriptively. The medicinal plants reviewed include Etlingera elatior, Cassia alata, Morinda citrifolia, Melaleuca leucadendra, Momordica charantia, Guazuma ulmifolia, Artocarpus altilis, Acacia nilotica, Gynura procumbens, Trigona incisa propolis, and Ficus carica. These plants contain secondary metabolites such as flavonoids, alkaloids, saponins, tannins, and phenols, which exhibit antibacterial activity by disrupting cell membranes, inhibiting protein synthesis, interfering with essential enzymes, and inducing oxidative stress in bacteria. The findings indicate that medicinal plants hold great potential as complementary or alternative therapies for pneumonia caused by antibiotic-resistant bacteria; however, further research, particularly in vivo and clinical studies, is required to confirm their efficacy and safety.